Annotated checklist of the freshwater fishes of continental and insular Honduras - Matamoros, Wilfredo A.; Schaefer, Jacob F.; Kreiser, Brian R. (Zootaxa, 2009)
The freshwater fishes of Honduras were surveyed for a period of four years (2005–2008). Surveys were supplemented with both literature and museum collection reviews. Our results show that there are at least 172 species of fishes inhabiting Honduran mainland and insular freshwater systems, 166 native and six exotic. Primary freshwater fish diversity was low, with only eigth species (4.8%). The remaining species were either secondary freshwater (47 species, 28.3%) or peripheral (111 species, 66.9%). This checklist includes 36 new records for Honduras, and 12 range expansions. Nine species were found to be endemic; however, just two of them (Amphilophus hogaboomorum and Theraps wesseli) are already described. The depauperate primary freshwater fishes fauna of Honduras (8) is congruent with low primary freshwater fishes diversity found in the region between the Usumacinta River and the Nicaraguan great lakes. Although many previously unsampled regions of Honduras were visited as part of this project, there are a variety of remote areas that remain unstudied. While this paper contributes much to the understanding of the distribution and diversity of Honduran freshwater fishes, it is likely that much diversity there remains undocumented.